Is vaccum formed retainor better than bonded retainer? Single blind, randomized controlled trial - Saba Habib; Waqas Ahmad Khan; Zubair Hassan Awaisi; Maria Manzoor (Medical Journal of South Punjab, 2025)
Objective: This prospective trial aimed to compare the clinical effectiveness of bonded retainers versus vacuum-formed retainers in maintaining lower arch alignment after orthodontic treatment over an 18-month period.Methodology: Study was conducted at orthodontic department of NID, Multan from June 2022 to December 2023. Patients having all treatment records including models, nearing end of orthodontic treatment, clinically satisfactory treatment results and alignment were included. A total of ninety patients included 45 patients in bonded retainer group and 45 in vacuum formed retainer group. Results: It was seen that little's irregularity index was relatively high in Group B than Group A, (p